Leptin hormone changes in patients with poly cystic ovarian syndrome treated by aromatase inhibitors - Al Omari, Wafa; Mustafa Al-Ahmad, Basma Ezzat (IIUM Press, International Islamic University Malaysia, 2018)
In the last few years a novel scope suggest the use of Aromatase inhibitors in women with PCOS (one of the most cause of anovulatory infertility) for treating the whole spectrum of reproductive, endocrine abnormalities usually found in such subject, particularly those who are classified as Clomiphene citrate resistant patients. On the other hand the discovery of Leptin hormone,a cytokine secreted by adipocytes, (167-amino acid peptide product of ob gene), generated an extraordinary interest in the understanding of the relationship between metabolic status and the neuroendocrine system, in particular, the neuroendocrine regulation of reproduction.